A new species of Metendothenia Diakonoff, 1973 (Lepidoptera: Tortricidae: Olethreutinae) from Thailand - Pinkaew, Nantasak; Muadsub, Sopita (Zootaxa, 2021)
Metendothenia chanthaboonica sp. nov. is described as new to science. Illustrations of the adult and genitalia are provided. The new taxon increases the number of described Metendothenia species to 16 worldwide, with four recorded from Thailand.